Jump to navigation Jump to search

General

Display information for equation id:math.63486.18 on revision:63486

* Page found: Results of Integrals with Coalescing Saddles (eq math.63486.18)

(force rerendering)

Cannot find the equation data in the database. Fetching from revision text.

Occurrences on the following pages:

Hash: 9486449e4e439a86362f9b504fcc5ce7

TeX (original user input):

P_{mn}(\mathbf{y}) = (t_{n}(\mathbf{x}(\mathbf{y})))^{K+1}+\sum_{l=m+2}^{K}\frac{l}{K+2}x_{l}(\mathbf{y})(t_{n}(\mathbf{x}(\mathbf{y})))^{l-1}

TeX (checked):

P_{mn}(\mathbf {y} )=(t_{n}(\mathbf {x} (\mathbf {y} )))^{K+1}+\sum _{l=m+2}^{K}{\frac {l}{K+2}}x_{l}(\mathbf {y} )(t_{n}(\mathbf {x} (\mathbf {y} )))^{l-1}

LaTeXML (experimental; uses MathML) rendering

MathML (15.098 KB / 2.063 KB) :

P m n ( 𝐲 ) = ( t n ( 𝐱 ( 𝐲 ) ) ) K + 1 + l = m + 2 K l K + 2 x l ( 𝐲 ) ( t n ( 𝐱 ( 𝐲 ) ) ) l - 1 subscript 𝑃 𝑚 𝑛 𝐲 superscript subscript 𝑡 𝑛 𝐱 𝐲 𝐾 1 superscript subscript 𝑙 𝑚 2 𝐾 𝑙 𝐾 2 subscript 𝑥 𝑙 𝐲 superscript subscript 𝑡 𝑛 𝐱 𝐲 𝑙 1 {\displaystyle{\displaystyle P_{mn}(\mathbf{y})=(t_{n}(\mathbf{x}(\mathbf{y}))% )^{K+1}+\sum_{l=m+2}^{K}\frac{l}{K+2}x_{l}(\mathbf{y})(t_{n}(\mathbf{x}(% \mathbf{y})))^{l-1}}}
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle{\displaystyle P_{mn}(\mathbf{y})=(t_{n}(\mathbf{x}(\mathbf{y}))%&#10;)^{K+1}+\sum_{l=m+2}^{K}\frac{l}{K+2}x_{l}(\mathbf{y})(t_{n}(\mathbf{x}(%&#10;\mathbf{y})))^{l-1}}}" display="inline">
  <semantics id="p1.1.m1.1a">
    <mrow id="p1.1.m1.1.39" xref="p1.1.m1.1.39.cmml">
      <mrow id="p1.1.m1.1.39.1" xref="p1.1.m1.1.39.1.cmml">
        <msub id="p1.1.m1.1.39.1.2" xref="p1.1.m1.1.39.1.2.cmml">
          <mi id="p1.1.m1.1.1" xref="p1.1.m1.1.1.cmml">P</mi>
          <mrow id="p1.1.m1.1.2.1" xref="p1.1.m1.1.2.1.cmml">
            <mi id="p1.1.m1.1.2.1.1" xref="p1.1.m1.1.2.1.1.cmml">m</mi>
            <mo id="p1.1.m1.1.2.1.3" xref="p1.1.m1.1.2.1.3.cmml"></mo>
            <mi id="p1.1.m1.1.2.1.2" xref="p1.1.m1.1.2.1.2.cmml">n</mi>
          </mrow>
        </msub>
        <mo id="p1.1.m1.1.39.1.1" xref="p1.1.m1.1.39.1.1.cmml"></mo>
        <mrow id="p1.1.m1.1.39.1.3" xref="p1.1.m1.1.39.1.cmml">
          <mo stretchy="false" id="p1.1.m1.1.3" xref="p1.1.m1.1.39.1.cmml">(</mo>
          <mi id="p1.1.m1.1.4" xref="p1.1.m1.1.4.cmml">𝐲</mi>
          <mo stretchy="false" id="p1.1.m1.1.5" xref="p1.1.m1.1.39.1.cmml">)</mo>
        </mrow>
      </mrow>
      <mo id="p1.1.m1.1.6" xref="p1.1.m1.1.6.cmml">=</mo>
      <mrow id="p1.1.m1.1.39.2" xref="p1.1.m1.1.39.2.cmml">
        <msup id="p1.1.m1.1.39.2.1" xref="p1.1.m1.1.39.2.1.cmml">
          <mrow id="p1.1.m1.1.39.2.1.2" xref="p1.1.m1.1.39.2.1.2.2.cmml">
            <mo stretchy="false" id="p1.1.m1.1.7" xref="p1.1.m1.1.39.2.1.2.2.cmml">(</mo>
            <mrow id="p1.1.m1.1.39.2.1.2.2" xref="p1.1.m1.1.39.2.1.2.2.cmml">
              <msub id="p1.1.m1.1.39.2.1.2.2.2" xref="p1.1.m1.1.39.2.1.2.2.2.cmml">
                <mi id="p1.1.m1.1.8" xref="p1.1.m1.1.8.cmml">t</mi>
                <mi id="p1.1.m1.1.9.1" xref="p1.1.m1.1.9.1.cmml">n</mi>
              </msub>
              <mo id="p1.1.m1.1.39.2.1.2.2.1" xref="p1.1.m1.1.39.2.1.2.2.1.cmml"></mo>
              <mrow id="p1.1.m1.1.39.2.1.2.2.3" xref="p1.1.m1.1.39.2.1.2.2.3.2.cmml">
                <mo stretchy="false" id="p1.1.m1.1.10" xref="p1.1.m1.1.39.2.1.2.2.3.2.cmml">(</mo>
                <mrow id="p1.1.m1.1.39.2.1.2.2.3.2" xref="p1.1.m1.1.39.2.1.2.2.3.2.cmml">
                  <mi id="p1.1.m1.1.11" xref="p1.1.m1.1.11.cmml">𝐱</mi>
                  <mo id="p1.1.m1.1.39.2.1.2.2.3.2.1" xref="p1.1.m1.1.39.2.1.2.2.3.2.1.cmml"></mo>
                  <mrow id="p1.1.m1.1.39.2.1.2.2.3.2.2" xref="p1.1.m1.1.39.2.1.2.2.3.2.cmml">
                    <mo stretchy="false" id="p1.1.m1.1.12" xref="p1.1.m1.1.39.2.1.2.2.3.2.cmml">(</mo>
                    <mi id="p1.1.m1.1.13" xref="p1.1.m1.1.13.cmml">𝐲</mi>
                    <mo stretchy="false" id="p1.1.m1.1.14" xref="p1.1.m1.1.39.2.1.2.2.3.2.cmml">)</mo>
                  </mrow>
                </mrow>
                <mo stretchy="false" id="p1.1.m1.1.15" xref="p1.1.m1.1.39.2.1.2.2.3.2.cmml">)</mo>
              </mrow>
            </mrow>
            <mo stretchy="false" id="p1.1.m1.1.16" xref="p1.1.m1.1.39.2.1.2.2.cmml">)</mo>
          </mrow>
          <mrow id="p1.1.m1.1.17.1" xref="p1.1.m1.1.17.1.cmml">
            <mi id="p1.1.m1.1.17.1.1" xref="p1.1.m1.1.17.1.1.cmml">K</mi>
            <mo id="p1.1.m1.1.17.1.2" xref="p1.1.m1.1.17.1.2.cmml">+</mo>
            <mn id="p1.1.m1.1.17.1.3" xref="p1.1.m1.1.17.1.3.cmml">1</mn>
          </mrow>
        </msup>
        <mo id="p1.1.m1.1.18" xref="p1.1.m1.1.18.cmml">+</mo>
        <mrow id="p1.1.m1.1.39.2.2" xref="p1.1.m1.1.39.2.2.cmml">
          <mstyle displaystyle="true" id="p1.1.m1.1.39.2.2.1" xref="p1.1.m1.1.39.2.2.1.cmml">
            <munderover id="p1.1.m1.1.39.2.2.1a" xref="p1.1.m1.1.39.2.2.1.cmml">
              <mo largeop="true" movablelimits="false" symmetric="true" id="p1.1.m1.1.19" xref="p1.1.m1.1.19.cmml"></mo>
              <mrow id="p1.1.m1.1.20.1" xref="p1.1.m1.1.20.1.cmml">
                <mi id="p1.1.m1.1.20.1.1" xref="p1.1.m1.1.20.1.1.cmml">l</mi>
                <mo id="p1.1.m1.1.20.1.2" xref="p1.1.m1.1.20.1.2.cmml">=</mo>
                <mrow id="p1.1.m1.1.20.1.6" xref="p1.1.m1.1.20.1.6.cmml">
                  <mi id="p1.1.m1.1.20.1.3" xref="p1.1.m1.1.20.1.3.cmml">m</mi>
                  <mo id="p1.1.m1.1.20.1.4" xref="p1.1.m1.1.20.1.4.cmml">+</mo>
                  <mn id="p1.1.m1.1.20.1.5" xref="p1.1.m1.1.20.1.5.cmml">2</mn>
                </mrow>
              </mrow>
              <mi id="p1.1.m1.1.21.1" xref="p1.1.m1.1.21.1.cmml">K</mi>
            </munderover>
          </mstyle>
          <mrow id="p1.1.m1.1.39.2.2.2" xref="p1.1.m1.1.39.2.2.2.cmml">
            <mstyle displaystyle="true" id="p1.1.m1.1.22" xref="p1.1.m1.1.22.cmml">
              <mfrac id="p1.1.m1.1.22a" xref="p1.1.m1.1.22.cmml">
                <mi id="p1.1.m1.1.22.2" xref="p1.1.m1.1.22.2.cmml">l</mi>
                <mrow id="p1.1.m1.1.22.3" xref="p1.1.m1.1.22.3.cmml">
                  <mi id="p1.1.m1.1.22.3.1" xref="p1.1.m1.1.22.3.1.cmml">K</mi>
                  <mo id="p1.1.m1.1.22.3.2" xref="p1.1.m1.1.22.3.2.cmml">+</mo>
                  <mn id="p1.1.m1.1.22.3.3" xref="p1.1.m1.1.22.3.3.cmml">2</mn>
                </mrow>
              </mfrac>
            </mstyle>
            <mo id="p1.1.m1.1.39.2.2.2.1" xref="p1.1.m1.1.39.2.2.2.1.cmml"></mo>
            <msub id="p1.1.m1.1.39.2.2.2.2" xref="p1.1.m1.1.39.2.2.2.2.cmml">
              <mi id="p1.1.m1.1.23" xref="p1.1.m1.1.23.cmml">x</mi>
              <mi id="p1.1.m1.1.24.1" xref="p1.1.m1.1.24.1.cmml">l</mi>
            </msub>
            <mo id="p1.1.m1.1.39.2.2.2.1a" xref="p1.1.m1.1.39.2.2.2.1.cmml"></mo>
            <mrow id="p1.1.m1.1.39.2.2.2.3" xref="p1.1.m1.1.39.2.2.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.25" xref="p1.1.m1.1.39.2.2.2.cmml">(</mo>
              <mi id="p1.1.m1.1.26" xref="p1.1.m1.1.26.cmml">𝐲</mi>
              <mo stretchy="false" id="p1.1.m1.1.27" xref="p1.1.m1.1.39.2.2.2.cmml">)</mo>
            </mrow>
            <mo id="p1.1.m1.1.39.2.2.2.1b" xref="p1.1.m1.1.39.2.2.2.1.cmml"></mo>
            <msup id="p1.1.m1.1.39.2.2.2.4" xref="p1.1.m1.1.39.2.2.2.4.cmml">
              <mrow id="p1.1.m1.1.39.2.2.2.4.2" xref="p1.1.m1.1.39.2.2.2.4.2.2.cmml">
                <mo stretchy="false" id="p1.1.m1.1.28" xref="p1.1.m1.1.39.2.2.2.4.2.2.cmml">(</mo>
                <mrow id="p1.1.m1.1.39.2.2.2.4.2.2" xref="p1.1.m1.1.39.2.2.2.4.2.2.cmml">
                  <msub id="p1.1.m1.1.39.2.2.2.4.2.2.2" xref="p1.1.m1.1.39.2.2.2.4.2.2.2.cmml">
                    <mi id="p1.1.m1.1.29" xref="p1.1.m1.1.29.cmml">t</mi>
                    <mi id="p1.1.m1.1.30.1" xref="p1.1.m1.1.30.1.cmml">n</mi>
                  </msub>
                  <mo id="p1.1.m1.1.39.2.2.2.4.2.2.1" xref="p1.1.m1.1.39.2.2.2.4.2.2.1.cmml"></mo>
                  <mrow id="p1.1.m1.1.39.2.2.2.4.2.2.3" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml">
                    <mo stretchy="false" id="p1.1.m1.1.31" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml">(</mo>
                    <mrow id="p1.1.m1.1.39.2.2.2.4.2.2.3.2" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml">
                      <mi id="p1.1.m1.1.32" xref="p1.1.m1.1.32.cmml">𝐱</mi>
                      <mo id="p1.1.m1.1.39.2.2.2.4.2.2.3.2.1" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.1.cmml"></mo>
                      <mrow id="p1.1.m1.1.39.2.2.2.4.2.2.3.2.2" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml">
                        <mo stretchy="false" id="p1.1.m1.1.33" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml">(</mo>
                        <mi id="p1.1.m1.1.34" xref="p1.1.m1.1.34.cmml">𝐲</mi>
                        <mo stretchy="false" id="p1.1.m1.1.35" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml">)</mo>
                      </mrow>
                    </mrow>
                    <mo stretchy="false" id="p1.1.m1.1.36" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml">)</mo>
                  </mrow>
                </mrow>
                <mo stretchy="false" id="p1.1.m1.1.37" xref="p1.1.m1.1.39.2.2.2.4.2.2.cmml">)</mo>
              </mrow>
              <mrow id="p1.1.m1.1.38.1" xref="p1.1.m1.1.38.1.cmml">
                <mi id="p1.1.m1.1.38.1.1" xref="p1.1.m1.1.38.1.1.cmml">l</mi>
                <mo id="p1.1.m1.1.38.1.2" xref="p1.1.m1.1.38.1.2.cmml">-</mo>
                <mn id="p1.1.m1.1.38.1.3" xref="p1.1.m1.1.38.1.3.cmml">1</mn>
              </mrow>
            </msup>
          </mrow>
        </mrow>
      </mrow>
    </mrow>
    <annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
      <apply id="p1.1.m1.1.39.cmml" xref="p1.1.m1.1.39">
        <eq id="p1.1.m1.1.6.cmml" xref="p1.1.m1.1.6"/>
        <apply id="p1.1.m1.1.39.1.cmml" xref="p1.1.m1.1.39.1">
          <times id="p1.1.m1.1.39.1.1.cmml" xref="p1.1.m1.1.39.1.1"/>
          <apply id="p1.1.m1.1.39.1.2.cmml" xref="p1.1.m1.1.39.1.2">
            <csymbol cd="ambiguous" id="p1.1.m1.1.39.1.2.1.cmml" xref="p1.1.m1.1.39.1.2">subscript</csymbol>
            <ci id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1">𝑃</ci>
            <apply id="p1.1.m1.1.2.1.cmml" xref="p1.1.m1.1.2.1">
              <times id="p1.1.m1.1.2.1.3.cmml" xref="p1.1.m1.1.2.1.3"/>
              <ci id="p1.1.m1.1.2.1.1.cmml" xref="p1.1.m1.1.2.1.1">𝑚</ci>
              <ci id="p1.1.m1.1.2.1.2.cmml" xref="p1.1.m1.1.2.1.2">𝑛</ci>
            </apply>
          </apply>
          <ci id="p1.1.m1.1.4.cmml" xref="p1.1.m1.1.4">𝐲</ci>
        </apply>
        <apply id="p1.1.m1.1.39.2.cmml" xref="p1.1.m1.1.39.2">
          <plus id="p1.1.m1.1.18.cmml" xref="p1.1.m1.1.18"/>
          <apply id="p1.1.m1.1.39.2.1.cmml" xref="p1.1.m1.1.39.2.1">
            <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.1.1.cmml" xref="p1.1.m1.1.39.2.1">superscript</csymbol>
            <apply id="p1.1.m1.1.39.2.1.2.2.cmml" xref="p1.1.m1.1.39.2.1.2">
              <times id="p1.1.m1.1.39.2.1.2.2.1.cmml" xref="p1.1.m1.1.39.2.1.2.2.1"/>
              <apply id="p1.1.m1.1.39.2.1.2.2.2.cmml" xref="p1.1.m1.1.39.2.1.2.2.2">
                <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.1.2.2.2.1.cmml" xref="p1.1.m1.1.39.2.1.2.2.2">subscript</csymbol>
                <ci id="p1.1.m1.1.8.cmml" xref="p1.1.m1.1.8">𝑡</ci>
                <ci id="p1.1.m1.1.9.1.cmml" xref="p1.1.m1.1.9.1">𝑛</ci>
              </apply>
              <apply id="p1.1.m1.1.39.2.1.2.2.3.2.cmml" xref="p1.1.m1.1.39.2.1.2.2.3">
                <times id="p1.1.m1.1.39.2.1.2.2.3.2.1.cmml" xref="p1.1.m1.1.39.2.1.2.2.3.2.1"/>
                <ci id="p1.1.m1.1.11.cmml" xref="p1.1.m1.1.11">𝐱</ci>
                <ci id="p1.1.m1.1.13.cmml" xref="p1.1.m1.1.13">𝐲</ci>
              </apply>
            </apply>
            <apply id="p1.1.m1.1.17.1.cmml" xref="p1.1.m1.1.17.1">
              <plus id="p1.1.m1.1.17.1.2.cmml" xref="p1.1.m1.1.17.1.2"/>
              <ci id="p1.1.m1.1.17.1.1.cmml" xref="p1.1.m1.1.17.1.1">𝐾</ci>
              <cn type="integer" id="p1.1.m1.1.17.1.3.cmml" xref="p1.1.m1.1.17.1.3">1</cn>
            </apply>
          </apply>
          <apply id="p1.1.m1.1.39.2.2.cmml" xref="p1.1.m1.1.39.2.2">
            <apply id="p1.1.m1.1.39.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.1">
              <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.2.1.1.cmml" xref="p1.1.m1.1.39.2.2.1">superscript</csymbol>
              <apply id="p1.1.m1.1.39.2.2.1.2.cmml" xref="p1.1.m1.1.39.2.2.1">
                <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.2.1.2.1.cmml" xref="p1.1.m1.1.39.2.2.1">subscript</csymbol>
                <sum id="p1.1.m1.1.19.cmml" xref="p1.1.m1.1.19"/>
                <apply id="p1.1.m1.1.20.1.cmml" xref="p1.1.m1.1.20.1">
                  <eq id="p1.1.m1.1.20.1.2.cmml" xref="p1.1.m1.1.20.1.2"/>
                  <ci id="p1.1.m1.1.20.1.1.cmml" xref="p1.1.m1.1.20.1.1">𝑙</ci>
                  <apply id="p1.1.m1.1.20.1.6.cmml" xref="p1.1.m1.1.20.1.6">
                    <plus id="p1.1.m1.1.20.1.4.cmml" xref="p1.1.m1.1.20.1.4"/>
                    <ci id="p1.1.m1.1.20.1.3.cmml" xref="p1.1.m1.1.20.1.3">𝑚</ci>
                    <cn type="integer" id="p1.1.m1.1.20.1.5.cmml" xref="p1.1.m1.1.20.1.5">2</cn>
                  </apply>
                </apply>
              </apply>
              <ci id="p1.1.m1.1.21.1.cmml" xref="p1.1.m1.1.21.1">𝐾</ci>
            </apply>
            <apply id="p1.1.m1.1.39.2.2.2.cmml" xref="p1.1.m1.1.39.2.2.2">
              <times id="p1.1.m1.1.39.2.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.2.1"/>
              <apply id="p1.1.m1.1.22.cmml" xref="p1.1.m1.1.22">
                <divide id="p1.1.m1.1.22.1.cmml" xref="p1.1.m1.1.22"/>
                <ci id="p1.1.m1.1.22.2.cmml" xref="p1.1.m1.1.22.2">𝑙</ci>
                <apply id="p1.1.m1.1.22.3.cmml" xref="p1.1.m1.1.22.3">
                  <plus id="p1.1.m1.1.22.3.2.cmml" xref="p1.1.m1.1.22.3.2"/>
                  <ci id="p1.1.m1.1.22.3.1.cmml" xref="p1.1.m1.1.22.3.1">𝐾</ci>
                  <cn type="integer" id="p1.1.m1.1.22.3.3.cmml" xref="p1.1.m1.1.22.3.3">2</cn>
                </apply>
              </apply>
              <apply id="p1.1.m1.1.39.2.2.2.2.cmml" xref="p1.1.m1.1.39.2.2.2.2">
                <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.2.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.2.2">subscript</csymbol>
                <ci id="p1.1.m1.1.23.cmml" xref="p1.1.m1.1.23">𝑥</ci>
                <ci id="p1.1.m1.1.24.1.cmml" xref="p1.1.m1.1.24.1">𝑙</ci>
              </apply>
              <ci id="p1.1.m1.1.26.cmml" xref="p1.1.m1.1.26">𝐲</ci>
              <apply id="p1.1.m1.1.39.2.2.2.4.cmml" xref="p1.1.m1.1.39.2.2.2.4">
                <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.2.2.4.1.cmml" xref="p1.1.m1.1.39.2.2.2.4">superscript</csymbol>
                <apply id="p1.1.m1.1.39.2.2.2.4.2.2.cmml" xref="p1.1.m1.1.39.2.2.2.4.2">
                  <times id="p1.1.m1.1.39.2.2.2.4.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.2.4.2.2.1"/>
                  <apply id="p1.1.m1.1.39.2.2.2.4.2.2.2.cmml" xref="p1.1.m1.1.39.2.2.2.4.2.2.2">
                    <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.2.2.4.2.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.2.4.2.2.2">subscript</csymbol>
                    <ci id="p1.1.m1.1.29.cmml" xref="p1.1.m1.1.29">𝑡</ci>
                    <ci id="p1.1.m1.1.30.1.cmml" xref="p1.1.m1.1.30.1">𝑛</ci>
                  </apply>
                  <apply id="p1.1.m1.1.39.2.2.2.4.2.2.3.2.cmml" xref="p1.1.m1.1.39.2.2.2.4.2.2.3">
                    <times id="p1.1.m1.1.39.2.2.2.4.2.2.3.2.1.cmml" xref="p1.1.m1.1.39.2.2.2.4.2.2.3.2.1"/>
                    <ci id="p1.1.m1.1.32.cmml" xref="p1.1.m1.1.32">𝐱</ci>
                    <ci id="p1.1.m1.1.34.cmml" xref="p1.1.m1.1.34">𝐲</ci>
                  </apply>
                </apply>
                <apply id="p1.1.m1.1.38.1.cmml" xref="p1.1.m1.1.38.1">
                  <minus id="p1.1.m1.1.38.1.2.cmml" xref="p1.1.m1.1.38.1.2"/>
                  <ci id="p1.1.m1.1.38.1.1.cmml" xref="p1.1.m1.1.38.1.1">𝑙</ci>
                  <cn type="integer" id="p1.1.m1.1.38.1.3.cmml" xref="p1.1.m1.1.38.1.3">1</cn>
                </apply>
              </apply>
            </apply>
          </apply>
        </apply>
      </apply>
    </annotation-xml>
    <annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle{\displaystyle P_{mn}(\mathbf{y})=(t_{n}(\mathbf{x}(\mathbf{y}))%
)^{K+1}+\sum_{l=m+2}^{K}\frac{l}{K+2}x_{l}(\mathbf{y})(t_{n}(\mathbf{x}(%
\mathbf{y})))^{l-1}}}</annotation>
  </semantics>
</math>

SVG (18.35 KB / 5.199 KB) :

{\displaystyle{\displaystyle P_{mn}(\mathbf{y})=(t_{n}(\mathbf{x}(\mathbf{y}))% )^{K+1}+\sum_{l=m+2}^{K}\frac{l}{K+2}x_{l}(\mathbf{y})(t_{n}(\mathbf{x}(% \mathbf{y})))^{l-1}}}

SVG with PNG fallback (MathML can be enabled via browser plugin) rendering

MathML (3.205 KB / 561 B) :

P m n ( y ) = ( t n ( x ( y ) ) ) K + 1 + l = m + 2 K l K + 2 x l ( y ) ( t n ( x ( y ) ) ) l 1 {\displaystyle P_{mn}(\mathbf {y} )=(t_{n}(\mathbf {x} (\mathbf {y} )))^{K+1}+\sum _{l=m+2}^{K}{\frac {l}{K+2}}x_{l}(\mathbf {y} )(t_{n}(\mathbf {x} (\mathbf {y} )))^{l-1}}
<math xmlns="http://www.w3.org/1998/Math/MathML" display="block" alttext="{\displaystyle P_{mn}(\mathbf {y} )=(t_{n}(\mathbf {x} (\mathbf {y} )))^{K+1}+\sum _{l=m+2}^{K}{\frac {l}{K+2}}x_{l}(\mathbf {y} )(t_{n}(\mathbf {x} (\mathbf {y} )))^{l-1}}">
  <semantics>
    <mrow class="MJX-TeXAtom-ORD">
      <mstyle displaystyle="true" scriptlevel="0">
        <msub>
          <mi>P</mi>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>m</mi>
            <mi>n</mi>
          </mrow>
        </msub>
        <mo stretchy="false">(</mo>
        <mrow class="MJX-TeXAtom-ORD">
          <mi mathvariant="bold">y</mi>
        </mrow>
        <mo stretchy="false">)</mo>
        <mo>=</mo>
        <mo stretchy="false">(</mo>
        <msub>
          <mi>t</mi>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>n</mi>
          </mrow>
        </msub>
        <mo stretchy="false">(</mo>
        <mrow class="MJX-TeXAtom-ORD">
          <mi mathvariant="bold">x</mi>
        </mrow>
        <mo stretchy="false">(</mo>
        <mrow class="MJX-TeXAtom-ORD">
          <mi mathvariant="bold">y</mi>
        </mrow>
        <mo stretchy="false">)</mo>
        <mo stretchy="false">)</mo>
        <msup>
          <mo stretchy="false">)</mo>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>K</mi>
            <mo>+</mo>
            <mn>1</mn>
          </mrow>
        </msup>
        <mo>+</mo>
        <munderover>
          <mo>&#x2211;<!-- ∑ --></mo>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>l</mi>
            <mo>=</mo>
            <mi>m</mi>
            <mo>+</mo>
            <mn>2</mn>
          </mrow>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>K</mi>
          </mrow>
        </munderover>
        <mrow class="MJX-TeXAtom-ORD">
          <mfrac>
            <mi>l</mi>
            <mrow>
              <mi>K</mi>
              <mo>+</mo>
              <mn>2</mn>
            </mrow>
          </mfrac>
        </mrow>
        <msub>
          <mi>x</mi>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>l</mi>
          </mrow>
        </msub>
        <mo stretchy="false">(</mo>
        <mrow class="MJX-TeXAtom-ORD">
          <mi mathvariant="bold">y</mi>
        </mrow>
        <mo stretchy="false">)</mo>
        <mo stretchy="false">(</mo>
        <msub>
          <mi>t</mi>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>n</mi>
          </mrow>
        </msub>
        <mo stretchy="false">(</mo>
        <mrow class="MJX-TeXAtom-ORD">
          <mi mathvariant="bold">x</mi>
        </mrow>
        <mo stretchy="false">(</mo>
        <mrow class="MJX-TeXAtom-ORD">
          <mi mathvariant="bold">y</mi>
        </mrow>
        <mo stretchy="false">)</mo>
        <mo stretchy="false">)</mo>
        <msup>
          <mo stretchy="false">)</mo>
          <mrow class="MJX-TeXAtom-ORD">
            <mi>l</mi>
            <mo>&#x2212;<!-- − --></mo>
            <mn>1</mn>
          </mrow>
        </msup>
      </mstyle>
    </mrow>
    <annotation encoding="application/x-tex">{\displaystyle P_{mn}(\mathbf {y} )=(t_{n}(\mathbf {x} (\mathbf {y} )))^{K+1}+\sum _{l=m+2}^{K}{\frac {l}{K+2}}x_{l}(\mathbf {y} )(t_{n}(\mathbf {x} (\mathbf {y} )))^{l-1}}</annotation>
  </semantics>
</math>

SVG (12.429 KB / 4.614 KB) :

{\displaystyle P_{mn}(\mathbf {y} )=(t_{n}(\mathbf {x} (\mathbf {y} )))^{K+1}+\sum _{l=m+2}^{K}{\frac {l}{K+2}}x_{l}(\mathbf {y} )(t_{n}(\mathbf {x} (\mathbf {y} )))^{l-1}}

PNG (0 B / 8 B) :


Translations to Computer Algebra Systems

Translation to Maple

In Maple:

Translation to Mathematica

In Mathematica:

Similar pages

Calculated based on the variables occurring on the entire Results of Integrals with Coalescing Saddles page

Identifiers

MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results